Health systems factors impacting the integration of midwifery: an evidence-informed framework on strengthening midwifery associations. Issue 6 (2nd June 2021) - Mattison, Cristina; Bourret, Kirsty; Hebert, Emmanuelle; Leshabari, Sebalda; Kabeya, Ambrocckha; Achiga, Patrick; Robinson, Jamie; Darling, Elizabeth
Abstract : Introduction: Midwifery associations are organisations that represent midwives and the profession of midwifery. They support midwives to reduce maternal and newborn mortality and morbidity by promoting the overall integration of midwifery in health systems. Our objective was to generate a framework for evidence-informed midwifery association strengthening. Methods: A critical interpretive synthesis complemented by key informant interviews, focus groups, observations, and document review was used to inform the development of concepts and theory. Three electronic bibliographical databases (CINAHL, EMBASE and MEDLINE) were searched through to 2 September 2020. A coding structure was created to guide the synthesis across the five sources of evidence. Results: A total of 1634 records were retrieved through electronic searches and 57 documents were included in the critical interpretive synthesis. Thirty-one (31) key informant interviews and five focus groups were completed including observations (255 pages) and audio recordings. Twenty-four (24) programme documents were reviewed. The resulting theoretical framework outlines the key factors by context, describes the system drivers that impact the sustainability of midwifery associations and identifies the key-enabling elements involved in designing programmes that strengthen midwifery associations. Conclusion: Midwifery associations act as the web that holds the profession together and are key to the integration of the profession in health systems, supporting enabling environments and improving gender inequities. Our findings highlight that in order to strengthen midwifery (education, regulation and services), we have to lead with association strengthening. Building strong associations is the foundation necessary to create formal quality midwifery education systems and to support midwifery regulation and accreditation mechanisms.